Inhibition of B‐cell apoptosis is mediated through increased expression of Bcl‐2 in patients with rheumatoid arthritis. (14th July 2015) - Yang, Jin; Zhao, Shaolin; Yang, Xinling; Zhang, Huanhuan; Zheng, Ping; Wu, Huiyi
Abstract: Aim: Abnormal B‐cell apoptosis is believed to have a role in rheumatoid arthritis (RA) pathogenesis, but the exact mechanisms of B‐cell apoptosis in RA have not been elucidated. We therefore investigated the percentage of circulating B cells and its relationship with apoptosis in a cohort of patients with RA. Methods: B cells were quantified by flow cytometry in RA patients and matched controls, and the relationships between these proportions and RA disease parameters were calculated. Rates of apoptosis were determined by annexin V/propidium iodine analysis, and Bcl‐2 and caspase‐3 protein levels were determined by western blot. Results: RA patients had significantly higher percentage of B cells in the peripheral blood than healthy controls but a significantly lower rate of B‐cell apoptosis. The percentage of B cells correlated with Disease Activity Score of 28 joints and serum immunoglobulin G concentration in RA patients. Expression of anti‐apoptosis protein Bcl‐2 was higher in RA patients than in healthy controls, whereas expression of apoptosis marker caspase‐3 in B cells was lower. Conclusion: The higher percentage of B cells in the peripheral blood of RA patients may be due, at least partially, to disruption of the normal pathway of apoptosis in these cells. The inhibition of B‐cell apoptosis in these patients may be attributable to the enhanced expression of Bcl‐2 in these cells.